2006
DOI: 10.1002/mrm.21052
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel density estimation in the human brain by means of dynamic contrast‐enhanced echo‐planar imaging

Abstract: Animal studies have shown that in vivo estimates of microvessel density in the brain may be obtained from an MRI-measurable index (Q) provided that a sufficiently high dose of an intravascular paramagnetic contrast agent is employed. Q is determined from the shifts in the transverse relaxation rates induced by the contrast agent, and a high dose is required for the validity of analytic expressions relating Q to the microvessel density. However, the steady-state imaging techniques used in these prior investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
61
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 23 publications
0
61
1
Order By: Relevance
“…One study has published a quantitative Q assessment in human brain tissue (Jensen et al, 2006). The Q values in our study are somewhat lower than those found by Jensen et al, in which a triple dose of contrast agent has been administered and only the maximum signal drop points are used to estimate Q.…”
Section: Feasibility Of Vessel Size Imaging In Acute Strokecontrasting
confidence: 78%
See 1 more Smart Citation
“…One study has published a quantitative Q assessment in human brain tissue (Jensen et al, 2006). The Q values in our study are somewhat lower than those found by Jensen et al, in which a triple dose of contrast agent has been administered and only the maximum signal drop points are used to estimate Q.…”
Section: Feasibility Of Vessel Size Imaging In Acute Strokecontrasting
confidence: 78%
“…In the mouse brain, k has been proposed as 329 s/mm 2 by Wu et al (2004), yet it is not available for the human brain. Jensen et al (2006) showed a possible way to calculate the lower and upper bounds of MVD in vivo by using Q. However, the lower and upper boundaries, which differ by two orders of magnitude, do not allow an accurate estimate of MVD.…”
Section: Feasibility Of Vessel Size Imaging In Acute Strokementioning
confidence: 99%
“…Analysis then showed that a scaled ratio, vessel density (Q) : DR 2 /(DR 2 *) 2/3 , correlated to histologic estimates of areal Q; this parameter has the advantage of being independent of the concentration of contrast agent present in the blood (18,19). Further development of this work resulted in a theoretical expression for vessel size index (VSI) (a weighted mean radius of all vessels contained within a voxel) that included the effects of diffusion and Dx, the susceptibility difference between blood and tissue due to the USPIO contrast agent (20).…”
mentioning
confidence: 99%
“…Although they lack the spatial and temporal resolution of optical methods, MRI methods can retrieve indirect information about the microcirculatory bed by using either magnetic susceptibility effects or blood displacement effects. Magnetic susceptibility effects can be used to probe the architecture of the microvasculature (9), whereas measuring the effects of blood displacement locally can be used to quantify perfusion (10) or directional blood transport (11). Techniques that measure perfusion rely on quantifying the terminal blood deposition, whereas techniques that measure blood transport rely on measuring certain parameters of the blood velocity distribution.…”
mentioning
confidence: 99%